MENILIK PEREMPUAN SEBAGAI SOCIAL CLIMBER DALAM PANDANGAN EKONOMI ISLAM - Nurudin, Nurudin; Muyassarah, Muyassarah (Pusat Studi gender dan Anak (PSGA) Universitas Islam Negeri Walisongo Semarang, 2017)
Social climber is described as a person who is eager to gain a higher social status in his or her society. In the globalization era, many women show off their styles that are not in accordance with their belongings. Those who look glamorous do not pay attention to the Islamic economic value. Therefore how women restrict the future generations not to be excessive in appearing their performance to avoid undesirable social and psychological impacts. Principally, Islam does not justify social climber because in Islamic economics istishod is recognized as the balance between the world and the hereafter which is in line with the Islamic economic goal namely al-falah. It means a balanced luck between the world and the hereafter. But it does not mean showing off glamorous behaviour in the world as such so it causes jealousy among the surrounding environment and induces criminals to commit crime such as theft, robbery and others. Social climber is also regarded as isrof means extravagance. Islamic economics forbids people to live extravagantly and miserly regardless of its impact because Islamic economics advocate simple life._________________________________________________________Social climber digambarkan sebagai seseorang yang ingin mendapatkan status sosial yang lebih tinggi di sekitarnya. Dalam kondisi zaman globalisasi banyak perempuan yang bergaya pamer tidak sesuai dengan kondisi materi yang dimilikinya. Mereka yang berpenampilan glamor tidak memperhatikan nilai-nilai ekonomi Islam. Oleh karena itu bagaimana para perempuan membatasi agar generasi-generasi mendatang tidak berlebihan dalam berpenampilan untuk menghindari dampak sosial dan psikologi yg tidak diinginkan. Pada prinsipnya, Islam tidak membenarkan social climber karena di dalam ekonomi Islam dikenal istilah istishod yakni keseimbangan antara dunia dan akhirat yang sejalan dengan tujuan ekonomi Islam yang disebut al-falah. Artinya keberuntungan yang seimbang antara dunia dan akhirat, jangan hanya untung dunia yang justru pamer atau berperilaku glamor yang menyebabkan kecemburuan lingkungan sekitar dan mengundang penjahat melakukan kejahatan misalnya pencurian, perampokan dan lain-lain. Social climber juga termasuk isrof yakni pemborosan. Ekonomi Islam melarang hidup boros berfoya-foya dan kikir tanpa memperhatikan dampaknya karena ekonomi Islam menganjurkan hidup sederhana.